2016
DOI: 10.1371/journal.pone.0150549
|View full text |Cite
|
Sign up to set email alerts
|

Soil Texture and Cultivar Effects on Rice (Oryza sativa, L.) Grain Yield, Yield Components and Water Productivity in Three Water Regimes

Abstract: The objective of this study was to determine the effects of water regime/soil condition (continuous flooding, saturated, and aerobic), cultivar (‘Cocodrie’ and ‘Rondo’), and soil texture (clay and sandy loam) on rice grain yield, yield components and water productivity using a greenhouse trial. Rice grain yield was significantly affected by soil texture and the interaction between water regime and cultivar. Significantly higher yield was obtained in continuous flooding than in aerobic and saturated soil condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 29 publications
(37 reference statements)
4
66
1
5
Order By: Relevance
“…They are coarse in texture and drain easily and quickly after the rain. It is lower in moisture-holding and nutrient-holding capacity than another type of soil (Dou et al, 2016). Sand negatively correlates silt and Ni in this study.…”
Section: Igbinosa Ih; Aisien Etcontrasting
confidence: 50%
“…They are coarse in texture and drain easily and quickly after the rain. It is lower in moisture-holding and nutrient-holding capacity than another type of soil (Dou et al, 2016). Sand negatively correlates silt and Ni in this study.…”
Section: Igbinosa Ih; Aisien Etcontrasting
confidence: 50%
“…De acordo com Galbieri et al (2014), no Estado de Mato Grosso, a produtividade de algodão não difere entre solos argilosos e de textura média. Dou et al (2016), relataram que solos argilosos possuem maior matéria orgânica quando comparados aos solos arenosos, isto ocorre devido à maior proteção física oferecida pela argila, ocorrendo menores perdas de matéria orgânica e consequentemente maior capacidade de água disponível à planta, o que proporcionou neste estudo, um acentuado aumento na produtividade da cultura do arroz.…”
Section: Materials E Métodos -Caracterização Dos Solos De Acordo Com Aunclassified
“…Increasing the clay content could improve the soil fertility [58]. A high biomass was recorded in rice grown in high clay soil than in rice grown in low clay soil [58][59][60]. In the present study, S (60%) showed a higher value for the dry weight of the leaves, stem, and spikelet, leading to the higher dry weight of the shoots than those in S (50%) and S (40%) ( Figure 5).…”
Section: Potassium Concentration In Plant Partitioningsmentioning
confidence: 44%
“…In addition to irrigation regimes, soil type could be another important factor that affects the biomass of rice. Increasing the clay content could improve the soil fertility [58]. A high biomass was recorded in rice grown in high clay soil than in rice grown in low clay soil [58][59][60].…”
Section: Potassium Concentration In Plant Partitioningsmentioning
confidence: 97%